Enhance formulation of organic coating for barrier protection of mild steel upon corrosive environment - Engku Norfatima, Engku Dahalan (2019)
Corrosion issues have been clearly marked in modern sciences as one of the factors that can trigger economic costs, technological delays as well as structural failures. The high content of pigment volume concentration (PVC) in organic coating offered better cathodic protection by sacrificed its active pigment to form a barrier protection to protect the steel from corroded. However, this technique came with several problems such as adhesion problem due to the low content of the binder, poor mechanical properties and a porous film which allowed the corrosive element to penetrate the coating layer thus, corroding the steel. Fly ash was introduced as new filler in this research to replaced kaolin in the coating due to the high content of alumina and silica compared to kaolin. The objectives of this research include comparing the formulated organic coating (kaolin as filler) with the commercial spray (corrosion factor 60) and to study the effectiveness of the parameters that influence the corrosion behaviour by using One Factor at Time (OFAT) method. The protection offered was compared among the formulated organic coatings (kaolin) and commercial spray. The parameters used in the OFAT method are PVC, the concentration of fly ash and the layers of the coatings. The adhesion observation was used to test the success and effectiveness of the coating formulation. The corrosion behaviour of the coating was studied by using electrochemical measurements and immersion test. Likewise, Scanning Electron Microscopy (SEM) and Thermal Gravimetric Analysis (TGA) were used in the study of the surface morphology and thermal behaviour of the coating. The responses from screening were fitted with a multiple linear regression equation and obtained a correlation (R² = 0.93) between the experimental data and model data. Analysis of variance (ANOVA) showed that the model is significant (P-value of 0.0026) for the total corrosion resistance. From the OFAT investigation on the organic coating with fly ash as filler, the low PVC had a good barrier protection compared to galvanic protection from high PVC. The addition of fly ash in the coating changed the properties of the coating from barrier to cathodic properties at low PVC. Therefore, the low PVC with a high content of fly ash (sample FA40) showed the best formulation of epoxy zinc coating with polarization resistance of 7.43E+9 Ω and corrosion rates of 2.17E-03 μm/yr. Overall, this study showed that the formulated organic coating (kaolin) possesses a barrier protection, whereas the commercial spray has good galvanic protection. Based on the result obtained from the OFAT analysis, it was found that the PVC plays an important role in corrosion behaviour compared to other parameters. On the other hand, the results from TGA measurement provided evidence that superior endurance can be offered by the fly ash.